2016
DOI: 10.1371/journal.pone.0156080
|View full text |Cite
|
Sign up to set email alerts
|

Rotational Stability of Scaphoid Osteosyntheses: An In Vitro Comparison of Small Fragment Cannulated Screws to Novel Bone Screw Sets

Abstract: BackgroundThe current standard of care for operative repair of scaphoid fractures involves reduction and internal fixation with a single headless compression screw. However, a compression screw in isolation does not necessarily control rotational stability at a fracture or nonunion site. The single screw provides rotational control through friction and bone interdigitation from compression at the fracture site. We hypothesize that osteosyntheses with novel bone screw sets (BSS) equipped with anti-rotational el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…However, Buetel tried to explain this contradictory result indicating that the screws used in the double screw combination were thin (1.5 mm). [9,10] Similar to the results of the study by Jurkowitsch et al, [9] the results of the current study showed that double screw fixation was superior to single screw in respect of both displacement and rotation. Although the diameter of the single screw is thicker than the double screw's, it has been shown to be weaker than two thin screws, particularly against rotational forces.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, Buetel tried to explain this contradictory result indicating that the screws used in the double screw combination were thin (1.5 mm). [9,10] Similar to the results of the study by Jurkowitsch et al, [9] the results of the current study showed that double screw fixation was superior to single screw in respect of both displacement and rotation. Although the diameter of the single screw is thicker than the double screw's, it has been shown to be weaker than two thin screws, particularly against rotational forces.…”
Section: Discussionsupporting
confidence: 89%
“…Biomechanical and clinical studies have shown that newly-developed scaphoid plates provide more stable fixation. [8,9] In addition, Erhart et al [10] have developed new anti-rotational screws particularly designed for scaphoid fractures.…”
mentioning
confidence: 99%
“…14 In addition, some of these studies only provided a vague idea of the efficacy of an in vivo osteosynthesis and thus, the use of specific screws still relies largely on availability, cost, and surgeon's preference. [15][16][17][18][19][20] The most prominent difference in the study was time to return to work between the two groups, favoring the operated group. A recent meta-analysis of four studies comparing operative (both open and percutaneous fixation) and conservative treatment of stable scaphoid fractures, reached the same conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have utilized a similar bending moment as a 800 N/mm moment is thought to be a clinically relevant load. 19,20 The bending moment was applied with a cantilever load on the proximal aspect where the cantilever load applied to the scaphoid depended on the moment arm which was measured as the horizontal distance between the midpoint of the fracture site and the location where cantilever load was applied. The cantilever load was calculated by dividing the bending moment of 800 N/mm by the moment arm.…”
Section: Methodsmentioning
confidence: 99%